Availability and readiness of the health facilities to provide HIV counseling and testing and prevention of mother-to-child transmission services in Burkina Faso: a trend analysis from 2012 to 2018 - Lucresse Corine Fassinou; Hervé Hien; Jean Cyr Yombi; Nicolas Nagot; Fati Kirakoya-Samadoulougou (BMC, 2023)
Abstract Background Provider-Initiated HIV Testing and Counseling (PITC) and Prevention of Mother-To-Child Transmission (PMTCT) are key services for achieving the goal of complete elimination of HIV. However, there is limited evidence on the ability of health facilities to provide these services in Burkina Faso. Therefore, we aimed to assess the trends and disparities in the availability and readiness of health facilities to provide PITC and PMTCT services in Burkina Faso between 2012 and 2018. Methods We performed a secondary analysis of facility-level data from the World Health Organization's Service Availability and Readiness Assessment (SARA) surveys conducted in 2012, 2014, 2016, and 2018 in Burkina Faso. The availability and readiness of health facilities were assessed using SARA's manual, and linear regressions were used to examine trends. Results Between 2012 and 2018, the mean proportion of health facilities providing PITC services increased, but not significantly, from 82.9% to 83.4% (p = 0.11), with the mean readiness index significantly decreasing from 71.5% to 65.4% (p < 0.001). This decrease concerned the staff and guidelines (73.8% to 50.5%; p < 0.001), equipment (79.0% to 77.4%; p < 0.001), and medicines and commodities (54.2% to 45.2%; p < 0.001) domains. Regarding the PMTCT services, the mean proportion of health facilities globally providing the service significantly decreased from 83.7% in 2012 to 67.7% (p = 0.030) in 2018, and the mean readiness significantly decreased from 53.2% in 2012 to 50.9% in 2018 (p = 0.004). This decreasing trend was related to the staff and training (80.3% to 57.6%; p < 0.001) and medicines and commodities (9.2% to 6.5%; p < 0.001) domains. The global significant negative trend of readiness was mainly observed at the primary level of healthcare (52.7% to 49.4%; p = 0.030). Four regions experienced a significant decrease in the readiness index of health facilities to provide PMTCT services: Cascades, Centre, Centre-Sud, and Sud-Ouest, while Haut-Bassins and Nord regions showed increasing trends. Conclusion Availability and readiness of health facilities to provide PITC and PMTCT remain suboptimal in Burkina Faso. Actions to strengthen the skills of professionals and enhance the availability of medicines and commodities while focusing more on health regions with significant decreasing trends are urgently needed to improve the quality of services for HIV.